Diagnostic performance of endoscopic ultrasonography‐guided elastography for solid pancreatic lesions: Shear‐wave measurements versus strain elastography with histogram analysis. Issue 4 (15th September 2020) - Ohno, Eizaburo; Kawashima, Hiroki; Ishikawa, Takuya; Iida, Tadashi; Suzuki, Hirotaka; Uetsuki, Kota; Yashika, Jun; Yamada, Kenta; Yoshikawa, Masakatsu; Gibo, Noriaki; Aoki, Toshinori; Kataoka, Kunio; et al.
Abstract : Background and aims: Endoscopic ultrasound (EUS) elastography (EUS‐EG) is a minimally invasive diagnostic method for evaluating tissue elasticity. The aim of this study was to evaluate the feasibility of newly developed EUS shear‐wave measurement (EUS‐SWM) and to compare diagnostic performance between EUS‐SWM and the conventional strain elastography (SE) for the measurement of elasticity of solid pancreatic lesions (SPLs). Methods: From December 2017 until August 2019, we retrospectively reviewed 64 consecutive cases with SPLs who underwent both EUS‐SWM and SE. EUS‐SWM was used to measure the shear‐wave velocity, Vs (m/s), and the unique measurement reliability index, VsN (%), in the target lesion. SE images were assessed by strain histogram (SH) analysis, and the mean strain value of the elasticity index was measured. We evaluated the diagnostic performance of EUS‐SWM and SE with SH to characterize the SPLs. Results: The Vs (m/s) values of SPLs were 2.19 for pancreatic cancer (PC), 1.31 for pancreatic neuroendocrine neoplasm (PanNEN), 2.56 for mass‐forming pancreatitis (MFP) and 1.58 for metastatic tumors. Vs showed no significant difference based on the disease. The mean strain values were 45.5 for PC, 47.3 for PanNEN, and 74.5 for MFP. In the comparison of tissue elasticity between PC and MFP, Vs showed no significant difference ( P = 0.5687); however, the mean strain value was significantly lower in PC cases (45.4 vs 74.5: P = 0.0007). Conclusion: Endoscopic ultrasound SWM tended to be unstable for the measurement of elasticity of SPLs, and conventional SE with SH was superior for their characterization.